'Expanded organoclay' assisted dispersion and simultaneous structural alterations of multiwall carbon nanotube (MWCNT) clusters in natural rubber. (11th February 2015) - Rooj, S.; Das, A.; Stöckelhuber, K.W.; Wießner, S.; Fischer, D.; Reuter, U.; Heinrich, G.
Abstract: We report about the successful 'expanded organoclay' (EMt) assisted dispersion of multiwall carbon nanotubes (MWCNT) and the subsequent synergy of both fillers in non-polar natural rubber (NR) compounds. Higher upward shifting of G band and substantial reduction of ID /IG ratio of MWCNT in the Raman spectroscopy in the presence of EMt was an indication of strong interactions between MWCNT and EMt particles which further improved the dispersion of MWCNT in the NR matrix. Attributed to the strong affinity of MWCNT with EMt we find significantly exfoliated EMt and homogeneously networked in these composites. The EMt driven dispersion of MWCNT, particularly at high content in the NR, was evidenced from transmission electron microscopy (TEM). The fractal dimension ( df ) of the MWCNT clusters in NR matrix both in the presence and absence of EMt was predicted utilizing the phenomenological Huber–Vilgis model. Interestingly, a lower value of df of MWCNT clusters was documented in the presence of EMt. Additionally, both the electrical and mechanical percolation threshold of MWCNT was reduced marginally with the addition of EMt.